2020
DOI: 10.3390/cells9020277
|View full text |Cite
|
Sign up to set email alerts
|

Norrin Protects Retinal Ganglion Cells from Excitotoxic Damage via the Induction of Leukemia Inhibitory Factor

Abstract: Purpose: To investigate whether and how leukemia inhibitory factor (Lif) is involved in mediating the neuroprotective effects of Norrin on retinal ganglion cells (RGC) following excitotoxic damage. Norrin is a secreted protein that protects RGC from N-methyl-d-aspartate (NMDA)-mediated excitotoxic damage, which is accompanied by increased expression of protective factors such as Lif, Edn2 and Fgf2. Methods: Lif-deficient mice were injected with NMDA in one eye and NMDA plus Norrin into the other eye. RGC damag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Another proposed mechanism of neuroprotection involves the leukemia inhibitory factor (LIF), which is necessary for the gliosis of Müller cells -a reaction of neural cells that contributes to the maintenance of retinal homeostasis in physiological and pathological states [104]. After excitotoxic damage, Norrin induces LIF expression in retinal neurons, which in turn stimulates Müller cells to secrete protective factors -endothelin 2 (ET-2) and fibroblast growth factor 2 (FGF2) [105].…”
Section: Norrinmentioning
confidence: 99%
“…Another proposed mechanism of neuroprotection involves the leukemia inhibitory factor (LIF), which is necessary for the gliosis of Müller cells -a reaction of neural cells that contributes to the maintenance of retinal homeostasis in physiological and pathological states [104]. After excitotoxic damage, Norrin induces LIF expression in retinal neurons, which in turn stimulates Müller cells to secrete protective factors -endothelin 2 (ET-2) and fibroblast growth factor 2 (FGF2) [105].…”
Section: Norrinmentioning
confidence: 99%
“…In the rd10 mouse retina, an RP mouse model, protective genes such as LIF, fgf2, and edn2 are also extensively upregulated [27]. Norrin, a secreted protein that protects retinal ganglion cells (RGCs) via LIF, is required to enhance Müller cell gliosis and induce protective factors such as Gfap, Edn2, and Fgf2 [28]. Such data lead to the hypothesis that fgf2 and edn2 are protective genes in Cep250 KO mice retina.…”
Section: Discussionmentioning
confidence: 99%
“…Norrin has also been known for its neuroprotective effects on RGCs following N-methyl-d-aspartate (NMDA)-mediated excitotoxic damage. The article in this issue by Kassumeh and colleagues [ 6 ] examines how leukemia inhibitory factor (Lif) is involved in this protective effect. The authors found that Müller cell gliosis, as well as endothelin 2 (Edn2) and fibroblast growth factor 2 (Fgf2) expression, was substantially blocked in Lif-deficient mice, indicating that Norrin exerts its protective effects through a Lif-dependent manner.…”
mentioning
confidence: 99%